Perimetry Update 1998/1999 - Wall, M.; Wild, J. M. (International Perimetric Society, 1999)
The topics presented at the XIIIth Symposium embraced all aspects of perimetric science. A total of ten sessions were held and covered: fundamentals of perimetry, visual psychophysics, new perimetric techniques, new algorithms for estimating threshold, perimetric variability, color perimetry, optic nerve head imaging, and visual field investigation in glaucoma and in retinal and neurological disorders. The new perimetric techniques included frequency doubling technology, flicker perimetry and pupil perimetry. The new algorithms included the Swedish Interactive Threshold Algorithm (SITA) and Te